The Effects of fire intensity on post-fire regeneration in Nawalpur District, Nepal - Shrestha, Nisha; Rai, Rajesh Kumar (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
Forest fires are one of the major ecological disturbances that affect forest composition, structure and regeneration patterns in Nepal's fire-prone habitats. In this study, post-fire regeneration patterns of forests in Nawalpur District, where repeated wildfires are increasingly threatening biodiversity, were examined. Based on MODIS satellite information and field observations of 217 sample plots, regeneration responses were analysed under varying fire intensities (very low, low, medium and high). The Kruskal–Wallis test revealed that sapling density, seedling density and total regeneration significantly varied among the fire intensities, whereas, species richness did not differ significantly. Canopy cover was significantly and positively correlated with species richness. Seedling density significantly declined in very low and low fire intensities but increased under moderate to high fire intensity, likely due to enhanced light availability and nutrient release following higher burn severity. In contrast, sapling density was higher in areas with very low fire intensity, possibly reflecting reduced mortality of established individuals. Regeneration felling and felling duration have no significant effect on regeneration. This research contributes to finer understanding of forest fire ecology in the Chure region of Nepal, providing region-specific insights that support the development of sustainable forest management policies. Long-term monitoring of forest fires, along with future research incorporating fire frequency, is imperative to fully understand forest resilience and recovery tracks in Nepal's